Elastoplasticité anisotrope non normale en grandes déformations avec endommagement: Application à la mise en forme des tôles minces - Badreddine, Houssem; Saanouni, Khémaïs; Dogui, Abdelwaheb; Gahbich, M. Amen (European Journal of Computational Mechanics, 2007)
This work is devoted to the numerical integration of an elastoplastic model strongly coupled with ductile damage and formulated in finite deformation. This model with mixed nonlinear work hardening (kinematic and isotropic) is based on a non associative and non normal plasticity theory. The integration is based on the elastic prediction – plastic correction procedure. The proposed constitutive models as well as the associated integration scheme are implemented into ABAQUS/Explicit thanks to VUMAT subroutine. The global resolution is done using the classical Dynamic Explicit (DE) strategy with ABAQUS/Explicit F.E. code. Application is made to the prediction of rupture in anisotropic thin sheet subjected to a hydro bulging test with circular and elliptic matrices. A conparison between the numerical and experimental results shows the capacity of such a modeling to reproduce the anisotropic thin sheet rupture.